Mycobacterial signaling through toll-like receptors - Basu, Joyoti; Shin, Dong-Min; Jo, Eun-Kyeong (Frontiers in Cellular and Infection Microbiology, 2012)
Studies over the past decade have helped to decipher molecular networks dependent on Toll-like receptor (TLR) signaling, in mycobacteria-infected macrophages. Stimulation of TLRs by mycobacteria and their antigenic components rapidly induces intracellular signaling cascades involved in the activation of nuclear factor-κB and mitogen-activated protein kinase pathways, which play important roles in orchestrating proinflammatory responses and innate defense through generation of a variety of antimicrobial effector molecules. Recent studies have provided evidence that mycobacterial TLR-signaling cross talks with other intracellular antimicrobial innate pathways, the autophagy process and functional vitamin D receptor signaling. In this article we describe recent advances in the recognition, responses, and regulation of mycobacterial signaling through TLRs.